Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1073/pnas.1506468112
|View full text |Cite
|
Sign up to set email alerts
|

Population, genetic, and antigenic diversity of the apicomplexanEimeria tenellaand their relevance to vaccine development

Abstract: The phylum Apicomplexa includes serious pathogens of humans and animals. Understanding the distribution and population structure of these protozoan parasites is of fundamental importance to explain disease epidemiology and develop sustainable controls. Predicting the likely efficacy and longevity of subunit vaccines in field populations relies on knowledge of relevant preexisting antigenic diversity, population structure, the likelihood of coinfection by genetically distinct strains, and the efficiency of cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
104
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 66 publications
(80 reference statements)
7
104
0
4
Order By: Relevance
“…Experimental recombinant or subunit vaccines have been described for many apicomplexans with varying levels of efficacy obtained under controlled laboratory or experimental animal conditions. However, commercial translation has commonly been hindered by a range of factors including naturally occurring genetic diversity in field parasites, resulting in insufficient immunological protection in the vaccinated host and selection of resistant populations (Dutta et al, 2007, Blake et al, 2015). If vaccines are to be successful and remain effective in the long term it is essential to understand the impacts that parasite genetic (antigenic) diversity and population structures have on the selection of field populations capable of vaccine escape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental recombinant or subunit vaccines have been described for many apicomplexans with varying levels of efficacy obtained under controlled laboratory or experimental animal conditions. However, commercial translation has commonly been hindered by a range of factors including naturally occurring genetic diversity in field parasites, resulting in insufficient immunological protection in the vaccinated host and selection of resistant populations (Dutta et al, 2007, Blake et al, 2015). If vaccines are to be successful and remain effective in the long term it is essential to understand the impacts that parasite genetic (antigenic) diversity and population structures have on the selection of field populations capable of vaccine escape.…”
Section: Introductionmentioning
confidence: 99%
“…For most other apicomplexans details on diversity are scarce; for example for Eimeria , the cause of the enteric disease coccidiosis, rather little is known at the molecular level. Recently, populations of Eimeria tenella parasites isolated from chicken facilities in Egypt, Libya, India and Nigeria were genotyped using a Sequenom MassARRAY single nucleotide polymorphism (SNP) tool, revealing notable variation in haplotype diversity and population structure with a North/South regional divide (Blake et al, 2015). E. tenella populations sampled below the 30th parallel north (30°N latitude) were defined by extensive haplotype diversity with no significant signatures of selection.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the chicken immune system recognizes the expressed viral proteins, which is a significant precedent to develop a vaccine in future, due to the chance to express antigens that allow recognition of the parasite. A study about the population structure or E. tenella as well as their genotype distribution and the presence of the Apical Membrane Antigen 1 (AMA1) showed that this antigen outweighs immune evasion [1].…”
Section: Future Vision Of Avian Coccidiosismentioning
confidence: 99%
“…About 60 billion chickens are produced worldwide every year. However, Eimeria protozoan parasites of Phylum Apicomplexa are considered the main risk to avian production since they are the causative agent of avian coccidiosis [1]. For Avian coccidiosis is caused by seven species of Eimeria, which parasite chickens intestine resulting in economic losses around $2.4 billion per year worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation